Do Neighborhood Effects on Low-Income Minority Children Depend on Their Age? Evidence From a Public Housing Natural Experiment. Issue 4 (4th July 2017) - Galster, George; Santiago, Anna Maria
Abstract: We analyze data from a natural experiment involving Denver public housing that quasirandomly assigns low-income Latino and African American youth to neighborhoods. Intent-to-treat and treatment-on-treated models reveal substantial effects of neighborhood socioeconomic status, ethnicity, and safety domains on youth and young adult educational, employment, and fertility outcomes. Effects are contingent on when a youth was first assigned to public housing and the neighborhood characteristic in question. Benefits from neighbors of higher occupational prestige are stronger if a child begins experiencing them at a younger age, whereas negative consequences of neighborhood crime are only manifested for teens. Neighborhood effect sizes apparently depend on the interaction among exposure duration, disruption effects of mobility, and developmental stage-specific differences in vulnerability to the given neighborhood effect mechanism operative. Our results hold powerful and provocative implications for where assisted housing should be developed and how applicants should be assigned to neighborhoods.